Arthroscopically Assisted Anterior Cruciate Ligament Reconstruction Using Bone-Patellar Tendon-Bone Autograft: Challenges and Solutions of Medial Independent Femoral Tunnel Drilling - Yazdan Raji MD; Ajit M. Vakharia MD; John T. Strony BS; Lakshmanan Sivasundaram MD; Nikunj N. Trivedi MD; Michael R. Karns MD; Michael J. Salata MD; James E. Voos MD (SAGE Publishing, 2021)
Background: As the main translational and rotatory stabilizer of the knee, the anterior cruciate ligament (ACL) plays a critical role in knee biomechanics. Anterior cruciate ligament ruptures generally require surgical attention for not only restoration of knee stability but also prevention of meniscal and chondral injuries. There are countless options for both the surgeon and the patient when contemplating graft choice and surgical technique for ACL reconstruction. However, the literature assessing the outcomes following various autografts has varied with some studies citing no significant difference in clinical and patient-reported outcomes, while others showing notable advantage when using bone-patellar tendon-bone (BPTB) autograft. In addition, there have been challenges associated with femoral tunnel placement using an anteromedial portal technique. Indications: In this study, we present a young female patient with a history of remote mid-substance ACL tear now presenting with worsening knee instability and a bucket-handle medial meniscus tear as a sequela of the incompetent ACL. After extensive discussion regarding the treatment options, patient had decided to proceed with surgical intervention with a BPTB autograft using the anteromedial portal technique for femoral tunnel placement and compression technique with bio-absorbable interference screw fixation. Results: Bone-patellar tendon-bone autograft has been noted to have lower risk of revision when compared with other graft options. Discussion: In this surgical technique study, we underline the importance of peritenon handling. We highlight the use of a 70-degree arthroscope to improve posterolateral wall visualization during femoral tunnel placement as well as for inspection of the reamed tibial tunnel. We also provide technique commentary and solutions for management of the medial femoral condyle (MFC) articular surface and femoral tunnel placement using an anteromedial portal technique. Last, we review graft-related outcomes, postoperative management, and rehabilitation protocol.